2017
DOI: 10.1093/jhps/hnx001
|View full text |Cite
|
Sign up to set email alerts
|

Labral reconstruction with tendon allograft: histological findings show revascularization at 8 weeks from implantation

Abstract: This description shows the histological findings of a peroneus brevis tendon allograft used for labral reconstruction, implanted 8 weeks before being retrieved due to a postoperative complication unrelated to the graft. As far as we have knowledge this is the first description about revascularization of an allograft used for hip labral reconstruction. The histological report of the removed peroneus brevis tendon allograft shows evidence of vascular ingrowth represented by small vessels with a thin muscular wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“… 23 Possible disadvantages of allograft use are disease transmission and delayed graft incorporation. 3 Moya Gómez et al 26 reported evidence of vascular ingrowth in all layers of the peroneus brevis allograft 8 weeks postoperatively, with cellular migration represented mainly by mature fibroblasts. While our study could not establish a clear preferred graft choice in terms of clinical outcomes, there was no known incidence of disease transmission, and patients in the ALLO group avoided any possibility of donor site morbidity.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Possible disadvantages of allograft use are disease transmission and delayed graft incorporation. 3 Moya Gómez et al 26 reported evidence of vascular ingrowth in all layers of the peroneus brevis allograft 8 weeks postoperatively, with cellular migration represented mainly by mature fibroblasts. While our study could not establish a clear preferred graft choice in terms of clinical outcomes, there was no known incidence of disease transmission, and patients in the ALLO group avoided any possibility of donor site morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Several techniques and graft options have been proposed for this treatment, and there is ample evidence of graft healing in such cases. 6,12,17,19,29,41…”
mentioning
confidence: 99%
“…Histological studies have confirmed that labral reconstruction allograft has shown signs of revascularization as early as 8 weeks postoperatively. 31 As a result, smoking in this critical early postoperative period may have detrimental effects on the revascularization process.…”
Section: Discussionmentioning
confidence: 99%